Reverse Current Treatment of Short Stacks – Experimental Results and System Considerations. (10th July 2019) - Hauck, Maximilian; Herrmann, Stephan; Hauser, Michael; Geiger, Andreas; Fischer, Felix; Weinrich, Jeremias; Gaderer, Matthias; Spliethoff, Hartmut
Abstract : Anode degradation is one of the main factors that limit the lifetime of solid oxide cells (SOCs), and thus complicate their commercial application. For nickel/yttria-stabilized-zirconia (Ni/YSZ) anodes, one possible counter measure is re-activation through reverse current treatment (RCT). This method has been described for single cells by other researchers. In order to investigate the applicability of RCT in SOC systems, we used this treatment on anode supported short stacks. Two stacks that had been exposed to different degradation phenomena were investigated. The first stack, suffering from partial re-oxidation and a cracked cell, already showed temporary performance improvement after electrolysis operation under mild conditions. The second stack had degraded over a thermal cycle, and different from the first one showed less re-activation. RCT under dry conditions was found to cause severe degradation. Furthermore, we found that, in agreement with literature, YSZ becomes electronically conductive during the RCT, meaning that electrolysis power during RCT is not limited by the amount of available steam. We discuss the issues of this behavior for SOC systems and possible solutions.